2017
DOI: 10.1186/s12877-017-0469-5
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood walkability, physical activity, and walking for transportation: A cross-sectional study of older adults living on low income

Abstract: BackgroundWalking, and in particular, outdoor walking, is the most common form of physical activity for older adults. To date, no study investigated the association between the neighborhood built environment and physical activity habits of older adults of low SES. Thus, our overarching aim was to examine the association between the neighborhood built environment and the spectrum of physical activity and walking for transportation in older adults of low socioeconomic status.MethodsCross-sectional data were from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 48 publications
4
85
0
Order By: Relevance
“…Older individuals’ behaviour is influenced by a confluence of environmental and individual factors . For older individuals facing functional decline, shopping itself is a challenge and difficult to do independently .…”
Section: Introductionmentioning
confidence: 99%
“…Older individuals’ behaviour is influenced by a confluence of environmental and individual factors . For older individuals facing functional decline, shopping itself is a challenge and difficult to do independently .…”
Section: Introductionmentioning
confidence: 99%
“…These strategies are fueled partly by research showing that people living in more walkable communities tend to be more physically active and weigh less (3)(4)(5)(6)(7)(8)(9)(10)(11). But the results in the literature are inconsistent (12)(13)(14)(15)(16). The correlation between neighborhood walkability and body weight seems to be different for men and women, as well as for older and younger people (3,5,6,17,18), and some studies have found no relationship between neighborhood walkability and body weight (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies using accelerometers with older adult participants have focused on associations of environment attributes with overall MVPA and LPA, but they did not examine associations with bout‐specific MVPA, overall SB, and prolonged SB . Hawkesworth et al ., for example, found that population density was unfavorably associated with LPA time, but walkability was not .…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of the present study include the use of objective measures of both walkability and activity outcomes, and descriptions of detailed activity patterns, which goes beyond previous studies examining associations with overall MVPA and LPA . We provided results from a seldom‐studied Asian population that differed from prior studies of associations of built environment with activity carried out primarily in Western countries.…”
Section: Discussionmentioning
confidence: 99%